Implementasi Pengelolaan Pendidikan Dalam Upaya Mengembangkan Kemampuan Berpikir Kreatif Siswa - Manurung, Alberth; Marini, Arita (Jurnal Elementaria Edukasia, 2023)
This study aims to describe the implementation of education management in an effort to develop students' creative thinking skills at SDN Kenari 07 Pagi in Mathematics. One of the advantages of managing education is that teachers are able to guide students in using the various concepts, principles and skills they have learned to solve the problems they are facing. With the implementation of educational management, the ability to think creatively can develop, because the creative thinking skills observed in this study are in the form of the ability to identify, analyze, solve problems, think logically and make decisions correctly and be able to draw conclusions